2018
DOI: 10.1074/jbc.ra118.003935
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor regulates mitochondrial dynamics and cell growth of human cancer cell lines through CD74–NF-κB signaling

Abstract: The indispensable role of macrophage migration inhibitory factor (MIF) in cancer cell proliferation is unambiguous, although which specific roles the cytokine plays to block apoptosis by preserving cell growth is still obscure. Using different cancer cell lines (AGS, HepG2, HCT116, and HeLa), here we report that the silencing of MIF severely deregulated mitochondrial structural dynamics by shifting the balance toward excess fission, besides inducing apoptosis with increasing sub-G 0 cells. Furthermore, enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…MIF is a pro-inflammatory cytokine that is widely expressed in many kinds of cells including MSCs [ 11 ]. Recent studies have shown that MIF plays an important role in cell survival and proliferation, and our previous study demonstrated that exosomes from MSCs with overexpression of MIF had better cardiac protection in rats with AMI [ 12 , 13 ]. In the present study, umbilical cord MSCs (ucMSCs) were infected with lentivirus containing MIF (MIF-MSC).…”
Section: Introductionmentioning
confidence: 99%
“…MIF is a pro-inflammatory cytokine that is widely expressed in many kinds of cells including MSCs [ 11 ]. Recent studies have shown that MIF plays an important role in cell survival and proliferation, and our previous study demonstrated that exosomes from MSCs with overexpression of MIF had better cardiac protection in rats with AMI [ 12 , 13 ]. In the present study, umbilical cord MSCs (ucMSCs) were infected with lentivirus containing MIF (MIF-MSC).…”
Section: Introductionmentioning
confidence: 99%
“…As expected, collagen proteins tightly connected GISTs and adipose endothelial cells spatially (Figure 5B). CD74 were found to be highly involved in such interactions by binding secreted proteins and cell surface receptors, such as MIF, APP, and COPA (Figure 5B), thus are likely to playing an important role in promoting tumor progression, according to previous research 45‐48 …”
Section: Resultsmentioning
confidence: 62%
“…CD74 were found to be highly involved in such interactions by binding secreted proteins and cell surface receptors, such as MIF, APP, and COPA ( Figure 5B), thus are likely to playing an important role in promoting tumor progression, according to previous research. [45][46][47][48] Additionally, we found some interactions uniquely from adipose endothelial cells ( Figure 5B, in the red boxes) that might affect tumor growth. First, adipose endothelial cells expressed LAGLS9…”
Section: Heterogeneity Of Nk Cells In Gistmentioning
confidence: 83%
“…Our previous study showed that exosomes from MSCs with overexpression of MIF compared with MSCs had better cardiac protection in rats with AMI. 12,13 In this study, we explored the mechanism of exosomes from MIF engineered umbilical cord MSCs (ucMSCs) in cardiac protective function. In vitro, we found that exosomes from MIF engineered ucMSCs (MIF-Exo) had the better effects of cell survival, blood vessel formation and cell migration than nonengineered ucMSCs (MSC-Exo).…”
Section: Introductionmentioning
confidence: 99%